The Influence of Peer Empathy on Final Assignment Completion Stress of Guidance and Counseling Students at Jambi University The Influence of Peer Empathy on Final Assignment Completion Stress of Guidance and Counseling Students at Jambi University - Putriyani, Imelda; Sutja, Akmal; Sarman, Freddi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This research is motivated by the belief that peer empathy is an important form of social support that helps reduce stress and encourages students to complete their final assignments. This support serves as a buffer against the stress felt by students. Therefore, this study aims to determine the effect of peer empathy on the stress of completing final assignments for Guidance and Counseling students at Jambi University. This study used a quantitative approach with an ex post facto method. The subjects were students of the Guidance and Counseling Study Program, batches of 2021 and 2022, at Jambi University. The data were then analyzed using statistical analysis with the help of SPSS. The study population was 144 students, with a sample of 106 students determined using the Slovin formula and a stratified sampling technique. Data collection used a Likert scale questionnaire that had been tested for validity and reliability, and was analyzed using a simple regression test in SPSS. The results showed that the level of peer empathy was in the high category with a percentage of 78.53%, while the level of stress in completing final assignments was in the medium category with a percentage of 58.12%. The analysis showed that peer empathy had a 63.9% effect on students' stress levels when completing their final assignments, while other factors contributed to the remaining 36.1%. Therefore, the greater the peer empathy, the lower the students' stress levels when completing their final assignments.